Animals should definitely not wear clothing. - Barrett, Judi. (New York : Macmillan Pub. Co., 1970)
Pictures of animals wearing clothes show why this would be a ridiculous custom for them to adopt.
Accelerated Reader AR
Keywords: Animals; American wit and humor